Developing a hydrological model for the Mekong Basin: impacts of basin development on fisheries productivity - Kite, Geoff (International Water Management Institute, 2000)
This report describes the hydrological aspects of a CGIAR project to model the effects of water flows on aquatic resource production in the Mekong Basin. The project was carried out by the International Centre for Living Aquatic Resources Management (ICLARM, Penang, Malaysia) and the International Water Management Institute (IWMI, Colombo, Sri Lanka) in cooperation with the Mekong River Commission (MRC, Phnom Penh, Cambodia) together with other institutes and national and regional agencies working in the riparian countries of Cambodia, Lao PDR, Thailand and Vietnam. The project commenced in January 2000 and finished in December 2000. The land cover analysis for the Tonle Sap area was carried out, and the data on existing and proposed dams were collated, by Dilkushi De Alwis, IWMI, Colombo.